High-fold improvement of assorted post-consumer poly(ethylene terephthalate) (PET) packages hydrolysis using Humicola insolens cutinase as a single biocatalyst. (June 2019) - Castro, Aline Machado de; Carniel, Adriano; Stahelin, Diego; Chinelatto Junior, Luiz Silvino; Honorato, Hercilio de Angeli; de Menezes, Sonia Maria Cabral
Graphical abstract: Highlights: Enzymatic poly(ethylene terephthalate) hydrolysis needs yield improvement. Humicola insolens cutinase is among the most efficient enzymes for depolymerization. The sequential approach included factorial designs and the path of steepest ascent. Terephthalic acid concentration and productivity were up to 20-fold increased. Abstract: The dissemination of technologies for poly(ethylene terephthalate) (PET) recycling is of paramount importance in the context of the plastics circular economy. One of the most promising alternatives is to use enzymes as catalysts for PET depolymerization to its monomers, but this route still needs improvement, especially regarding titer and productivity. In the present work, a sequential approach comprised of fractional factorial and central composite rotatable designs, the path of steepest ascent and one-way evaluation of variable effect, was performed to address these limitations, during assorted post-consumer PET (PC-PET) hydrolysis catalyzed by Humicola insolens cutinase. The highest terephthalic acid concentration and productivity during PC-PET hydrolysis were 100.9 mM (16.8 g/L) and 14.4 mM/day, corresponding to overall improvements of 10-fold and 20-fold, respectively. These data are among the best results described so far for enzyme-catalyzed hydrolysis of used PET packages. Also, the use of a single enzyme system, instead of multiple biocatalysts to achieve final conversion of PET to its monomers, lowers the process complexity and costs.